(untitled) (Research, Society and Development, 2020)
Teaching in the early years for teaching mathematics is still a challenge and there are still research gaps in this regard. This scenario generated the motivation for this study, but being the broad theme, we delimited for this article, contributions from a study group on the teaching and learning of Mathematics from the point of view of Critical Mathematical Education. For this article, the goal is to disseminate what has already been accomplished, through the exchange of ideas and collaborative studies, on the Critical Mathematics Education proposal in the early years. The scientific initiation research, in progress, takes place with students of Pedagogy, Administration and graduate of Mathematics and Information Systems at Faculdade Estácio de Vitória, Espírito Santo. It is formative, exploratory, descriptive and qualitative. Data is collected from video recording of remote meetings, file and review of articles, as well as survey and presentation of teaching practices. The initial results point to proposals for teaching practices that already reflect the initial studies of Critical Mathematical Education.